Describing rosé: An embedding-based method for measuring preferences - MUKHERJEE, Anirban (Institutional Knowledge at Singapore Management University, 2022)
In this paper, we present a novel preference-measurement method for experiential products and develop a novel embedding-based utility model to value product attributes and attribute-levels from participant choices between products described in (unstructured) prose.